2016
DOI: 10.1097/rlu.0000000000000988
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Comparative Study of Parathyroid Dual-Phase Scintigraphy, Dual-Isotope Subtraction Scintigraphy, 4D-CT, and Ultrasonography in Primary Hyperparathyroidism

Abstract: Dual isotope pinhole subtraction PS has higher diagnostic accuracy compared with dual-phase PS, 4D-CT, and US as a first-line imaging study in primary hyperparathyroidism. In case of a negative scintigraphy or suspicion of multiglandular disease, 4D-CT and/or US is recommended as a second-line modality. However, diagnostic algorithms should be adapted in accordance with local availability and expertise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 31 publications
0
47
3
1
Order By: Relevance
“…The DP protocol had higher sensitivity than the DT and DTDP protocols. This finding is contrary to most previous studies that reported that dual tracer had higher sensitivity than single tracer protocols [20][21][22][23][24][25][26][27]. The discrepant finding in the current study could, to some degree, be due to context bias since most of the patients sent for parathyroid scintigraphy at the authors' center have end-stage renal disease with pronounced hyperparathyroidism.…”
Section: Discussioncontrasting
confidence: 99%
“…The DP protocol had higher sensitivity than the DT and DTDP protocols. This finding is contrary to most previous studies that reported that dual tracer had higher sensitivity than single tracer protocols [20][21][22][23][24][25][26][27]. The discrepant finding in the current study could, to some degree, be due to context bias since most of the patients sent for parathyroid scintigraphy at the authors' center have end-stage renal disease with pronounced hyperparathyroidism.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, the sensitivity of high‐resolution US was slightly lower in our study (51.8%) compared with the 78.5% to 85% sensitivity achieved by others, probably because the images were obtained by different radiologists, an issue that may contribute to greater interobserver variability. However, several studies found lower sensitivity for high‐resolution US, such as those by Kobylecka et al, Yao et al, and Krakauer et al, with values of 44%, 49%, and 57%, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…Heiba et al 22 compared neck pinhole dual-tracer and dualphase sestamibi with and without SPECT for localization of 153 parathyroid adenomas, and they found that pinhole dual-tracer SPECT had significantly higher sensitivity (93%) than dual-phase SPECT (68%), SPECT with only pinhole delay (39%), pinhole dual-tracer CT alone (25%), and dual-phase CT alone (18%). In a prospective study comparing dual-isotope subtraction pinhole scintigraphy, dual-phase SPECT, 4DCT, and sonography in 91 patients with 97 parathyroid adenomas, Krakauer et al 23 found that the sensitivity of dual-isotope subtraction pinhole scintigraphy was 93%. The sensitivity of dual-phase SPECT (65%), 4DCT (58%), and sonography (57%) was significantly lower.…”
Section: Discussionmentioning
confidence: 99%